ANCANG BANGUN ENERGI TERBARUKAN BAGI INDUSTRI PERTAHANAN GUNA MENDUKUNG PELAKSANAAN PERANG BERLARUT - Nur Aini Putri (DAS Institute, 2022)
The defense industry is important in national defense, therefore energy security is needed. The purpose of this study is to analyze the threat of energy security in the event of a protracted war and the potential for solar energy. The method used in this research is to use PSVsyst in the design of PLTS. The results of energy security at PT Pindad only come from PLN 5,540 kVA and 3,465 kVA, Then for emergencies, PT Pindad has 2 Genset Units with a maximum capacity of 1.8 MW. With this situation, there is a threat of energy security in the event of a protracted war, namely the decision to supply electricity from PLN. Therefore, energy security is needed with the construction of PLTS in the PT Pindad area. From the data, PT Pindad's one hour electricity demand is 6,591 kWh/m2 and the building area that can be used for solar cell roof area is 33,775 m2 at PT Pindad.